Republic of Niger : Measuring Poverty Trends - World Bank (Washington, DC, 2015)
Accurately measuring poverty and assessing trends in its incidence and severity are among the most fundamental challenges in economic development. The issue of effective poverty measurement has been the subject of renewed interest since the United Nations adopted the millennium development goals (MDGs) in 2000. In Niger, as in many comparable countries worldwide, poverty data are collected through household surveys of consumption patterns and living conditions. A number of methodological factors can affect the accuracy of consumption data during the collection phase, especially the number of survey visits, the time of year during which the questionnaire is administered, the recall period, and the composition of the consumption basket defined in the survey. The purpose of this paper is to produce a robust analysis of poverty trends in Niger from 2005 to 2011 by using the 2011 survey as the basis for monitoring poverty and correcting for methodological differences in earlier surveys. The decision to use the 2011 survey as the basis for establishing methodological consistency is rooted in two factors. First, the large variations in poverty estimates obtained in different survey periods are suspected to be due in part to changes in the survey methodology. Second, the 2011 survey coincided with the adoption of Niger’s current growth and poverty reduction strategy, programme de développement economique et social (PDES). The report describes the 2011 survey methodology and the techniques used to make the previous figures compatible with this methodology. It presents the revised poverty figures and discusses their implications. It also offers conclusions and recommendations.